Heat transfer effects on free convection of viscous dissipative fluid flow over an inclined plate with thermal radiation in the presence of induced magnetic field - Kumar, P. Pramod; Malga, Bala Siddulu; Appidi, Lakshmi; Matta, Sweta (Zielona Góra: Uniwersytet Zielonogórski)
The principal objective of the present paper is to know the reaction of thermal radiation and the effects of magnetic fields on a viscous dissipative free convection fluid flow past an inclined infinite plate in the presence of an induced magnetic field.
Keywords: thermal radiation; induced magnetic field; magnetic Prandtl number; free convection; Galerkin finite element method; viscous dissipation